Pretransplant hypoalbuminemia may be associated with poor survival in patients that underwent autologous hematopoietic stem cell transplantation (autoHSCT) - Serdar Sivgin; Suleyman Baldane; Leylagul Kaynar; Fatih Kurnaz; Muzaffer Keklik; Cigdem Pala; Gokmen Zararsiz; Bulent Eser; Mustafa Cetin; Ali Unal (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
Objectives and aim: Serum albumin level is mainly a marker of nutritional status in both healthy subjects and patients with malignancies. Our objective was to investigate the association of pre-transplant serum albumin levels with prognosis in autologous HSCT recipients.